Multilingualism and gendered immigrant identity : perspectives from Catalonia - Ali, Farah, 1985- (Bristol, UK ; Jackson, TN : Multilingual Matters, 2023)
"This book examines the intersectionality of gendered, religious identity among Muslim women in Catalonia, and illustrates how this identity is brokered through language use in a multilingual and diasporic context. It offers a unique lens through which we can further our understanding of the role of language in the acculturation process"--
Language use and language policy in Catalonia -- Acculturation and negotiating identity -- Research design -- Spaniard on purpose : narratives of first-generation informants -- In two worlds : narratives of second-generation informants -- Catalan, Spanish, and heritage languages : reported language use and attitudes -- Implications for sociolinguistic research -- Implications for language and immigrant-targeted policies -- Appendix A: Questionnaire -- Appendix B: Interview questions.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on October 25, 2022).
JSTOR
Keywords: Women immigrants -- Spain -- Catalonia -- Social conditions; Muslim women -- Spain -- Catalonia -- Social conditions; Catalan language -- Social aspects; Group identity -- Spain -- Catalonia; Intersectionality (Sociology) -- Spain -- Catalonia; Immigrantes -- Espagne -- Catalogne -- Conditions sociales; Musulmanes -- Espagne -- Catalogne -- Conditions sociales; Catalan (Langue) -- Aspect social; Identité collective -- Espagne -- Catalogne; Intersectionnalité -- Espagne -- Catalogne; SOCIAL SCIENCE / Emigration & Immigration; Catalan language -- Social aspects; Group identity; Intersectionality (Sociology); Muslim women -- Social conditions; Women immigrants -- Social conditions; Spain -- Catalonia